ANALISIS EFEKTIFITAS PEMANFAATAN KREDIT DALAM PENGEMBANGAN USAHA MIKRO, KECIL, DAN MENENGAH PADA CREDIT UNION KHATULISTIWA BAKTI KANTOR PELAYANAN JERUJU PONTIANAK - B21112051, Retno Susanti (Jurnal Curvanomic, 2016)
The title of this research is Credit Utilization Effectiveness Analysis to The Development of Micro, Small and Medium Trading In The Khatulistiwa Bakti Credit Union Services Office On Jeruju Pontianak. The aim of this research to discovered about how the credit utilization effectiveness to the development of micro, small and medium trading (UMKM) in the Khatulistiwa Bakti Credit Union services office on Jeruju Pontianak. The method which used was analysis descriptive qualitative method with primary data. The population which used in this research were subject of micro, small and medium trading (UMKM) Â Khatulistiwa Bakti Credit Union Services Office On Jeruju Pontianak the number of 186 subjects. The number of research sample was 33 subjects, used Purposive Sampling method. The data collected by using a questionnaire (questionnaire). Result of this research showed that the effectiveness after got credit which gived by Khatulistiwa Bakti Credit Union that used to development (Capital) trading people in UMKM with approval level or precentage about 80,03%. The increasing of trading capital made the turover of trade as significantly has increased and indirectly gain this trading has increased in range of between 60% < X â‰¤ 80% in effectiveness catagory. Keyword : effectiveness, micro, small and medium trading (UMKM), Capital, Turnover, gain.